IMPLEMENTATION OF LASAMBA BAKERY INDEPENDENCE ACTIVITIES IN INCREASING WORK MOTIVATION OF PRISONERS IN SALEMBA PRISON - Arbi, Muhamad Ar Rafii; Rohayati, Ade Cici (Universitas Nusa Cendana, 2025)
This study aims to examine the implementation of the Lasamba Bakery vocational training program at Class IIA Salemba Correctional Facility, where the goal is to enhance inmate work motivation through bread-making skills training. The program provides inmates with the opportunity to develop practical skills that will be beneficial after their release. The study employs a qualitative method. In its implementation, communication, resources, disposition, and bureaucratic structure play crucial roles. Although socialization and communication have been conducted through various channels, including inmate interactions, challenges persist, particularly concerning inmate perceptions of the quantity and price of bread. Other obstacles, such as limited resources and specialized training, also need to be addressed to support the smooth operation of the program. With improved socialization and resource management, the program is expected to continue running effectively and positively impact the inmates' motivation and work skills. Keywords: Vocational Training; Work Motivation; Prison